2012
DOI: 10.1089/ees.2011.0070
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Critical Factors Related to Summer Chlorophyll a Concentration in the Sueo Dam Reservoir, Republic of Korea

Abstract: This study examined critical factors related to the short-term variation of algae growth in reservoirs during the summer. To this end, statistical tests were carried out at a small dam reservoir to determine how chemical factors (e.g., nutrient concentrations) and physical factors (e.g., theoretical and relative residence times, temperature) influenced the chlorophyll a (Chl-a) concentration. Statistical tests revealed that, although phosphorus (P) concentration was significant for Chl-a, residence time had mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Dickman, [20] showed that increased water residence time more likely increases the algae bloom, especially for small reservoirs. Several other works showed that Chl-a increases with increasing residence time and decreases with increasing discharge [21,22]. The hydrological residence time in our study area was expected to increase during the lockdown period owing to following reasons: (i) sewage disposal to the lakes has completely stopped, causing reduced discharge via inlets, and (ii) all anthropogenic activities, including boating has stopped during the lockdown period, causing still waters.…”
Section: Theoretical Frameworkmentioning
confidence: 85%
“…Dickman, [20] showed that increased water residence time more likely increases the algae bloom, especially for small reservoirs. Several other works showed that Chl-a increases with increasing residence time and decreases with increasing discharge [21,22]. The hydrological residence time in our study area was expected to increase during the lockdown period owing to following reasons: (i) sewage disposal to the lakes has completely stopped, causing reduced discharge via inlets, and (ii) all anthropogenic activities, including boating has stopped during the lockdown period, causing still waters.…”
Section: Theoretical Frameworkmentioning
confidence: 85%
“…Flushing rate, measured as the water volume stored in the reservoir divided by the volumetric flowrate (Straškraba, Dostálková, Hejzlar, & Vyhnálek, 1995), is a widely used index of nutrient depletion in reservoirs. Many studies have reported the effects of hydraulic retention time (or hydraulic residence time) on the phytoplankton biomass and eutrophication (Kawara, Yura, Fujii, & Matsumoto, 1998;Lee et al, 2012). Groeger and Kimmel (1984) reported that the allochthonous nutrient inputs in lakes and reservoirs were negative logarithmically related to the hydraulic residence time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such complex systems must be operated considering not only water quantity, but residence time as a factor that can improve water quality, minimizing primary production and possibly cyanobacterial blooms. Lee's study (Lee et al, 2012) of a Korean reservoir raised the possibility of inhibiting algae growth establishing strategies for water quality management, such as diminishing the residence time in summer. …”
Section: Discussionmentioning
confidence: 99%